A note on weakly quasi continuous functions - Jin Han Park; Hoe Young Ha (International Journal of Mathematics and Mathematical Sciences)
The notion of weakly quasi continuous functions introduced by Popa and Stan [1]. In this paper, the authors obtain the further properties of such functions and introduce weak* quasi continuity which is weaker than semi continuity [2] but independent ofweak quasi continuity.